CIK as therapeutic agents against tumors. (December 2017) - Introna, M.
Abstract: Cytokine Induced Killer (CIK) cells are ex vivo expanded and activated T lymphocytes obtained by sequential incubation of Peripheral Blood Mononuclear cells (PBMNC) with Interferon γ (IFNG), anti CD3 monoclonal antibody OKT3 and IL2. These cells, while retaining few characteristics of the Effector memory T cells subpopulation, acquired during culture CD56 expression, as well as non specific, Natural Killer like, anti tumoral cytotoxicity. CIK cells from human are equivalent to expanded NKT cells in mouse. More interestingly, CIK cells show a potent intratumoral homing in several experimental models, followed by anti tumoral clinical activity in mice and humans. In spite of extensive in vivo permanence and proliferation, CIK cells do not show cytotoxicity against normal targets and, particularly important, do not show Graft versus host disease when tested in allogeneic combinations (donor versus host) even in the haploidentical matching. For the easiness of the laboratory preparations, the availability of clinical grade reagents, the production of Good Manufacturing Practice compliant methods, CIK cells have been extensively used for the treatment of cancer patients, in both hematologic and solid tumors, in both autologous and allogeneic combinations. Several clinical protocol will be here discussed and summarised to show the feasibility of these passive transfer approaches, and also their very limited toxicity. Finally, preliminary indications on clinical efficacy, particularly in hematologic malignancies and against minimal residual disease, will be shown and discussed, as well as the future perspectives to optimize this adoptive passive cell immunotherapy strategy by gene transfer technology or bispecific monoclonal antibodies addition. Highlights: Cytokine Induced Killer (CIK) cells are T-EMRA CD8 + lymphocytes which express CD56. CIK cells show intratumoral homing and antitumoral activity. CIK cells can be used in autologous as well as allogeneic combination without toxicity. The standard protocol for CIK preparation is GMP compliant.